PRINSIP REKRUTMEN HAKIM PENGADILAN PAJAK PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 26/PUU-XXI/2023: The Fundamental of Recruitment Tax Court Post Constitutional Court Decision Number 26/PUU-XXI/2023 - Evanto Pandora Manalu (Jurnal Hukum PRIORIS, 2024)
Constitutional Court Decision Number 26/PUU-XXI/2023 mandates a shift in the authority of an institution, namely the Tax Court under the Supreme Court. Apart from relates the organizational governance, finance and administration of the Tax Court was previously led by the Ministry of finance Republic Indonesia, of course the recruitment of tax judges relates all the required terms and conditions. For this reason, a guideline is needed in the process of procuring tax judges in accordance with the mandate of the Constitutional Court Decision Number 26/PUU-XXI/2023 in accordance with the procurement of judges previously regulated by the Supreme Court in accordance with applicable laws and regulations. The fundamental of recruiting tax judges hopely there will be a method and determination of the qualifications of more qualified judges considering that the Supreme Court will become a new vessel for tax judges generally as well general court, religion court, administration court, military court. It also hoped that the procurement and recruitment of tax judges will not only emphasize capability and quality in tax acknowledge but also prioritize aspects of legal knowledge or capability in examining cases carried out by judges under Supreme Court.